EFEKTIFITAS PUPUK FOSFAT TERHADAP PRODUKTIVITAS KACANG TANAH (Arachis hypogaea L.) PADA ULTISOL GLEE GAPUI - Yasier, Ibnu; Nasrullah, Nasrullah; Karnilawati, Karnilawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2023)
Peanut is a food crop that has economic value and has high protein. This study aims to determine the effect of the effectiveness of phosphate fertilizers on the productivity of peanuts. This research was conducted at the Experimental Garden of the Faculty of Agriculture, Universitas Jabal Ghafur, starting from February to June 2023. This study used a randomized block design with a non-factorial pattern, namely the dose of phosphate control, 5 g/plant, 10 g/plant, and 15 g/plant. The results showed that the best dose of phosphate fertilizer was found in the 5 g/plant treatment and had a very significant effect on the number of fruits per plant, the weight of the pods per plant and the number of fruits per plant. The best dose use was found in the 5 g/plant treatment. It is suspected that the 5 g/plant dose of phosphate fertilizer is more efficient than the use of other phosphate fertilizer doses.Keywords : Peanut, Phosphate Fertilizer, Ultisol.